VARIABLES AND MECHANISM OF TECHNICAL AND ECONOMIC FEASIBILITY EVALUATION FOR ESTABLISHING PROPOSED TOMATO PASTE FACTORY IN RAMADI, ANBAR - AL-DULEIMI , Hammed RASHEED; Abbas, Ahmed A. (Diyala Agricultural Sciences Journal, 2013)
The present study depends on an analytical approach supported by practical applications to obtain the required results for the production of tomato paste without underestimating the economic part, since the case demands a faith in the necessity to adopt the scientific thoughts and their translation into practice in reality. The study stems from a hypothesis that the economic evaluation of investment projects aims to give the investor free choice among the available chances according to scientific bases and standards which assure overcoming the mysterious and foggy state , removing the distress annoying him in order to be more comfortable and able to adopt a scientific and economic approach and explain the vision set ahead to be more realistic in making the suitable and right decision to arrive at the best alternatives that could lower the costs and insure better economic return from the project under investment. Analysis of the expected investment according to money flow (input and output) expected during the proposed duration of the project is important in making the right decision concerning investment opportunities and determining the most efficient and most profitable flows. The present study has determined the basic requirements and necessary costs (investment and working) in addition to the labor necessary for the project. Consequently , economic evaluation was done . The study showed that the net annual incomes reached 2322.27 million dinners , the total additive value was 2528.52 million dinners and the net additive value was 2379.87 million dinners. Also , the study revealed that the return of invested dinner in the project was about 42% and the period necessary for the project in recovering investment costs was about 3 years. The study could arrive at some recommendations necessary for encouraging investment in this field